THE OPTIMIZATION OF SCIENTIFIC APPROACH THROUGH OUTDOOR LEARNING WITH SCHOOL YARD BASIS - Wijayanti, Astuti; Munandar, Aris (Unnes Science Education Journal, 2017)
Abstract ___________________________________________________________________ Inquiry cannot be separated in learning science activities. Students are actively involved in constructing knowledge of both hands-on and minds-on. Learning science will be more meaningful when students can get to know the material science is not in the form of textual but contextual where students can learn science closer to the event / phenomenon that occurs in the factual and the environment around them more real. The science acquisition process can be conducted using a scientific approach that is packed with outdoor learning. This article is the result of the study of literature on school-based learning outdoor yard (neighborhood school) which is expected to facilitate teachers in applying scientific approaches and outdoor learning so that students can be closer to the surrounding environment.